A flexible characterization methodology of RRAM: Application to the modeling of the conductivity changes as synaptic weight updates. (September 2019) - Pedro, M.; Martin-Martinez, J.; Rodriguez, R.; Gonzalez, M.B.; Campabadal, F.; Nafria, M.
Abstract: In this work, an automatic and flexible measurement setup, which allows a massive electrical characterization of single RRAM devices with pulsed voltages, is presented. The evaluation of the G-V maps under single-pulse test-schemes is introduced as an example of application of the proposed methodology, in particular for neuromorphic engineering, where the fine analog control of the synaptic device conductivity state is required, by inducing small changes in each learning iteration. To describe the obtained data, a time-independent compact model for memristive devices is used. The fitting parameters statistical distributions are further studied.